Erythrocyte Sedimentation Rate (with its inherent limitations) Remains a Useful Investigation in Contemporary Clinical Practice - Kahar, Manoj A (Annals of Pathology and Laboratory Medicine, 2022)
Erythrocyte Sedimentation Rate(ESR) determined by Westergren method is used in diagnosis and monitoring inflammatory activities. Extremely elevated ESR (>100mm/hr) is usually indicative of a serious underlying disease. ESR phenomenon occurs in three phases (Aggregation, Decantation & Packaging) and is related to certain laws of physics like Stokesâ€™s law. ESR by Westergren method is affected by RBC, Plasma and Technical factors and also by many physiological and clinical states. ESR by Westergren method is endorsed by International Council for Standardization in Haematology as a â€œGold Standardâ€ for ESR determination and provides recommendations to perform ESR by reference method. ESR by conventional Westergren method has many limitations necessitating technical innovations and alternate test methods in ESR determination.